OPTIMALISASI PROFIL BAJA IWF PADA BANGUNAN GUDANG KONSTRUKSI GABLE FRAME BERDASARKAN SNI 1729:2015 - Putri, Ardini Yuliastri; Bayzoni, Bayzoni; Widyawati, Ratna (Universitas Lampung, 2017)
The increasement and development of economic growth in Indonesia cause increasement of the construction of warehouse to support business expansion. However, there is an opinion about expensive steel prices which is causes the use of the steel its self is not optimum. In this case, there must be a calculation to determine the model of gable frame and the dimension of steel profiles for the warehouse. In this study, the frame model is limited of four types that have differences in haunch span. This study also use the Direct Stiffness Method to calculate structural analysis and SNI 1729: 2015 to calculate section analysis. From structural and section analysis, obtained weight for each type of frame. Frame Type 1 has 4.771,89 kg, Frame Type 2 has 3.348,18 kg, Frame Type 3 has 3.682,24 kg and Frame Type 4 has 10.541,1506 kg. Based on the volume and weight calculation in each frame type, Frame Type 2 has the lowest weight. Hence, this type of portal can be considered as the most optimum portal type. Key word : gable frame construction, SNI 1729: 2015, Direct Stiffness Method